2005
DOI: 10.1007/s00429-004-0450-x
|View full text |Cite
|
Sign up to set email alerts
|

The axon arbourisation of nuclei isthmi neurons in the optic tectum of the chick and pigeon. A Golgi and anterograde tracer-study

Abstract: The optic tectum is reciprocally connected to the nuclei isthmi pars magnocellularis (Imc) and pars parvocellularis (Ipc), which have different modulatory effects on optic transmission. We studied the axon arbourisation of these isthmic nuclei in the optic tectum in order to differentiate between them using Golgi-impregnated preparations both in chickens and pigeons. In addition, sections from animals injected with the anterograde tracer biotinylated dextran-amine (BDA) into the Imc were examined in the bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…A terminal varicosity in layer 10 described by Ramón y Cajal (1911) in sparrows was not seen in the current study. Two major variations of Ipc brush-like endings were observed in the current tracing studies and may correspond to the long and short axonal arborizations identified by Tömböl et al (1995Tömböl et al ( , 20051998), although our observation does not support their previous suggestion that short and long endings, respectively, arise from Ipc and Imc. The light, diffuse projection from Ipc on the deep tectal layers 11-13 was first identified in our PHA-L tracing studies and further confirmed with intracellular filling of individual Ipc neurons.…”
Section: Columnar Axonal Terminations Of Ipc and Slu Neuronscontrasting
confidence: 61%
“…A terminal varicosity in layer 10 described by Ramón y Cajal (1911) in sparrows was not seen in the current study. Two major variations of Ipc brush-like endings were observed in the current tracing studies and may correspond to the long and short axonal arborizations identified by Tömböl et al (1995Tömböl et al ( , 20051998), although our observation does not support their previous suggestion that short and long endings, respectively, arise from Ipc and Imc. The light, diffuse projection from Ipc on the deep tectal layers 11-13 was first identified in our PHA-L tracing studies and further confirmed with intracellular filling of individual Ipc neurons.…”
Section: Columnar Axonal Terminations Of Ipc and Slu Neuronscontrasting
confidence: 61%